Synthesis, structures and bioinorganic aspects of organotin derivatives / Lee See Mun - Lee, See Mun (2011)

(untitled)
Metal complexes are widely prepared and have been successfully used in the treatment of numerous human diseases including cancer. Organotin complexes are also studied due to their potential biological activities such as anticancer, antihistamine, antifungal, biocides and anti-fouling. In addition, Schiff base ligands derived from substituted salicylaldehyde and substituted 2-hydroxyacetophenone are found to be biologically active as anticancer and antimicrobial agents. It is therefore the focus of this research project to investigate the variation of biological activity of the diorganotin Schiff base complexes in relation to their structures. In the present studies, several series of Schiff base ligands were prepared with salicylaldehyde, substituted salicylaldehyde, 2-hydroxyacetophenone and substituted 2-hydroxyacetophenone. The diorganotin complexes were subsequently prepared by reacting the ligands with diorganotin dichloride or oxide in 1:1 molar ratio and were characterized by various spectroscopic methods including IR, NMR and UV spectroscopies. The structures of the selected diorganotin complexes were determined by X-ray crystallography and will be briefly discussed. The in vitro cytotoxic activity of the Schiff base ligands and their diorganotin complexes had been evaluated against several cancer cell-lines such as HT-29, SKOV-3 and MCF-7. In general, the cytotoxic activity test showed that the diorganotin complexes had better cytotoxic activity as compared to the Schiff base ligands.